2018
DOI: 10.14421/skijic.v1i1.1217
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Tarekat Communities and Social Changes in Indonesian History

Abstract: Islam as a religious system is generally based on three principal teachings called as aqidah (theology), syari'ah (law), and tasawwuf (Sufism, moral and spiritual). Each thought and the Islamic expertise have also established Muslim communities that demonstrate the diversity of social and religious history in various regions on the spread of Islam. In the history of the spread of Islam in Indonesia, particularly the Sufis always showed a significant role in each period of social change. Therefore, further disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One of the spiritual practices in Berlian Mas that must be done by a salik to get love from God is to love the motherland and with the Nahdlatul Ulama flag. This may be affected by the history that in the early 20th century, the social power of the tarekat people became an indicator of religion resurgence, which had a significant impact on Indonesia's nationalistic movement (Abdurahman, 2018).…”
Section: Kendalisada's Spiritual Practice Aims To Get Closermentioning
confidence: 99%
“…One of the spiritual practices in Berlian Mas that must be done by a salik to get love from God is to love the motherland and with the Nahdlatul Ulama flag. This may be affected by the history that in the early 20th century, the social power of the tarekat people became an indicator of religion resurgence, which had a significant impact on Indonesia's nationalistic movement (Abdurahman, 2018).…”
Section: Kendalisada's Spiritual Practice Aims To Get Closermentioning
confidence: 99%
“…First, a study that explains the teachings and practices of the tarekat (Azwar, 2018;Habiba Abror et al, 2021;Ziadi, 2018). Second, tarekat is a response to the problems of today's society (Abdullah, 2018;Abdurahman, 2018;Hamzah & Nasrul, 2020;Kertayasa et al, 2021;Shadiqin, 2018). In this case, the tarekat teaching in building religious awareness responds to the erosion of moral and spiritual values (Jamaludin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by scholars on the role of tariqa in society has shown that tariqa plays an essential role in social, cultural, and political life in the Islamic world, including in Indonesia [3][4][5]. Studies on tariqa in Indonesia have been conducted extensively, including studies on the origins and development of Sufism in Southeast Asia, particularly in Indonesia [6][7][8][9][10][11][12]. However, research related to the role of the tariqa in viewing social and cultural change in Indonesia, including Lombok, has yet to be explicitly explored.…”
Section: Introductionmentioning
confidence: 99%